Influencia de la inteligencia emocional en el rendimiento académico de los estudiantes de la Unidad Educativa Francisco Huerta Rendón de la cuidad de Babahoyo - Arellano Véliz, Jennifer (2025)
Emotional intelligence in educational institutions has become one of the priorities, due to the impact of this factor on both comprehensive development and academic performance. Some training centers prioritize emotional development to obtain quality education. The objective of this study is to assess the influence of emotional intelligence on the academic performance of students at the Francisco Huerta Rendón Educational Unit in the city of Babahoyo. The methodology used was a non-experimental, cross-sectional design study, the types of research were documentary and field. The methods used were inductive and deductive. The technique to be used was a psychosomatic test and document analysis. The thunderclaps were the Mezquite – Mayer Test and registration and registration sheet. The results showed that: The level of emotional intelligence of the students of the Francisco Huerta Rendón Educational Unit in the city of Babahoyo is high (84% high, 16% moderate); However, it is necessary to highlight that there were no levels of low or gifted emotional intelligence, a scenario that reveals that all students are within the common average.